A review of the associations between obstructive sleep apnea and hypertensive disorders of pregnancy and possible mechanisms of disease. (December 2018) - Dominguez, Jennifer E.; Habib, Ashraf S.; Krystal, Andrew D.
Summary: Obesity is prevalent among pregnant women in the United States; 15–20% of obese pregnant women have obstructive sleep apnea. The prevalence of obstructive sleep apnea increases along with body mass index, age and in the presence of other co-morbidities. Untreated obstructive sleep apnea in women is associated with a range of cardiovascular, pulmonary and metabolic co-morbidities; recent studies suggest that women with obstructive sleep apnea in pregnancy may be at significantly greater risk of entering pregnancy with chronic hypertension and/or of developing hypertensive disorders of pregnancy: gestational hypertension; preeclampsia; or eclampsia. This has serious public health implications; hypertensive disorders of pregnancy are a major cause of maternal and neonatal morbidity and mortality and are associated with a greater lifetime risk for cardiovascular disease. The mechanisms that associated obstructive sleep apnea with hypertensive disorders of pregnancy have not been defined, but several pathways are scientifically plausible. In this review, we will present a comprehensive literature review of the following: the associations between obstructive sleep apnea and hypertensive disorders of pregnancy; the proposed mechanisms that may connect obstructive sleep apnea and hypertensive disorders of pregnancy; and the effectiveness of treatment at mitigating these adverse outcomes.